104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Howard Watkins, Brad Geery, Judge Dwayne Keyes receiving $10,000 check from Fresno County Young Lawyers Association for the Fresno County Law Library; Judy Soley and William J. Smith Judge Keyes chaired the Board of Directors for the Law Library